2015
DOI: 10.1097/qad.0000000000000784
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Ebola epidemic on general and HIV care in Macenta, Forest Guinea, 2014

Abstract: Objective The current Ebola epidemic massively affected the Macenta district in Forest Guinea. We aimed at investigating its impact on general and HIV care at the only HIV care facility in the district. Design Prospective observational single-facility study Methods Routinely collected data on use of general hospital services and HIV care were linked to Ebola surveillance data published by the Guinea Ministry of Health. In addition we compared retention among HIV-infected patients enrolled into care in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 12 publications
1
47
0
Order By: Relevance
“…21 This decline was similar to that observed with HIV and TB diagnoses in Guinea. 22 Furthermore, the 'no touch' policy 6 may have discouraged HIV testing due to its invasive nature. The marked decline in HIV testing in highly Ebola-affected counties may have …”
Section: Discussionmentioning
confidence: 99%
“…21 This decline was similar to that observed with HIV and TB diagnoses in Guinea. 22 Furthermore, the 'no touch' policy 6 may have discouraged HIV testing due to its invasive nature. The marked decline in HIV testing in highly Ebola-affected counties may have …”
Section: Discussionmentioning
confidence: 99%
“…9 In Macenta, Forested Guinea, where the Ebola outbreak started and which was severely affected by Ebola, there was an overall decline in reporting of new TB cases. 10 By contrast, in Guinea's capital city, Conakry, where there were fewer Ebola cases and non-governmental organisations (NGOs) provided support in the form of a package of measures to guarantee a continuum of care, TB case finding and services were maintained at satisfactory levels. 11 These reports, and the lack of published information to date from Sierra Leone, suggest that more information is needed about the extent to which the Ebola virus outbreak disrupted TB control programme services.…”
mentioning
confidence: 99%
“…One study from Sierra Leone showed a drop in surgical interventions associated with the Ebola outbreak, 9 while others have shown declines in out-patient consultations for malaria, 10 reduced attendance of reproductive health services 11 and deterioration in the quality of chronic care. 12 In Sierra Leone, malaria and respiratory infections are the most common morbidities among children aged < 5 years. 13 As both of these conditions present with fever, which overlaps with the symptoms of Ebola virus disease, anecdotal evidence shows that parents might have avoided bringing their children to health facilities due to fears of being labelled as an Ebola case.…”
mentioning
confidence: 99%